EVALUATION OF INTERNATİONAL FINANCIAL CENTERS AND ISTANBUL FINANCIAL CENTER PROJECT IN THE PERSPECTIVE OF GLOBAL CITY INDICES (Third Sector Social Economic Review, 2022)
In this study, the current situation of Istanbul, which aims to become one of the international financial centers with the Istanbul Financial Center project, according to the criteria of global city indices, and its feasibility as a financial center in the medium-long term were investigated. A comparison of international financial centers and Istanbul has been made and its potential has been revealed. According to the GFCI 30 City Profiles International Diversity Index, Istanbul; It succeeded to be in the first place, leaving behind cities such as Tel Aviv, Mexico City and Helsinki. But in line with the results achieved; It does not seem possible for Istanbul to be an international financial center at the moment. The city's ability to reach the level of a global financial center; It depends on the further development of its positive features and the elimination of its current disadvantages over time by minimizing it.
Keywords: Finance; Financial Centers; Istanbul Financial Center; Global City Indices; GFCI.